Ultra-large area graphene hybrid hydrogel for customized performance supercapacitors: High volumetric, areal energy density and potential wearability. (1st February 2020) - Sikdar, Anirban; Majumdar, Abhisek; Dutta, Pronoy; Borah, Munu; Kim, Sang Ouk; Maiti, Uday Narayan
Abstract: Volumetric and areal energy densities are the key performance metrics for electrochemical supercapacitors (EC) used in portable storage devices, whereas mechanical flexibility and potential for direct integration with conventional cloths are the primary requirements for wearable usage. Herein, highly scalable, versatile EC electrodes are presented based on the spontaneously assembled hydrogel-hybrids of graphene and polyaniline (PANI). Our hydrogel-hybrids exhibit areal capacitance of 853 mF cm −2 (at 1 mA cm −2 ) with superb cycling stability (95.2% retention after 5000 cycles), which can be readily increased up to 2.2 F cm −2  by the multistacking of electrodes without sacrificing charging-discharging rate capability. Control of hydration level (water < 35 wt%) by means of simple mechanical compression leads to remarkably high volumetric capacitance of 560 F cm −3, while retaining high areal value and rate capability. Moreover, requirement for wearable EC can easily be realized via direct integration of hydrogel-hybrids with carbon cloths. Such a noticeable performance of our hybrid devices is largely owing to the nanoporous graphene framework that offers continuous electronic conduction pathways as well as hydrated ion channels for the effective access to PANI-nanowire surfaces. Graphical abstract: Image 1